2017
DOI: 10.2147/ijn.s140835
|View full text |Cite
|
Sign up to set email alerts
|

Design, optimization and characterization of coenzyme Q10- and D-panthenyl triacetate-loaded liposomes

Abstract: Coenzyme Q10 (CoQ10) is a lipid-soluble molecule found naturally in many eukaryotic cells and is essential for electron transport chain and energy generation in mitochondria. D-Panthenyl triacetate (PTA) is an oil-soluble derivative of D-panthenol, which is essential for coenzyme A synthesis in the epithelium. Liposomal formulations that encapsulate both ingredients were prepared and optimized by applying response surface methodology for increased stability and skin penetration. The optimum formulation compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…0.20 ± 0.001 indicated homogeneous population of liposomes (Table 2). This was in accordance with the studies of other authors who also achieved to develop Q 10 -loaded liposomes of particle size less than 200 nm and of satisfactory homogeneity [29,30]. The storage of liposomes LD1 at different temperatures (4 °C, RT and 40 °C) for 6 months revealed that their particle size did not change significantly when they were stored at 4 °C and RT, compared to their initial values.…”
Section: Characterization and Stability Evaluation Of The Q 10 -Loaded Liposome Dispersionssupporting
confidence: 92%
“…0.20 ± 0.001 indicated homogeneous population of liposomes (Table 2). This was in accordance with the studies of other authors who also achieved to develop Q 10 -loaded liposomes of particle size less than 200 nm and of satisfactory homogeneity [29,30]. The storage of liposomes LD1 at different temperatures (4 °C, RT and 40 °C) for 6 months revealed that their particle size did not change significantly when they were stored at 4 °C and RT, compared to their initial values.…”
Section: Characterization and Stability Evaluation Of The Q 10 -Loaded Liposome Dispersionssupporting
confidence: 92%
“…S4 ). The aqueous solubility of CoQ 10 by itself is reported to be around 0.7 ng/ml [ 66 ]. Therefore, a CoQ 10 concentration of >2 mM indicates an >2.4 × 10 6 fold increase of solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Response was predicted by the following quadratic polynomial equation ( Equation 4 ): where Y represents the predicted response, A and B indicate the independent variables, β 0 is the intercept value, β 1 and β 2 are linear coefficients of the model, β 12 is interaction coefficient, while β 11 and β 22 are quadratic coefficients. 28 , 29 …”
Section: Methodsmentioning
confidence: 99%